Acquisition of iron by Aeromonas salmonicida. - Chart, H (1983)
The ability of six typical and three atypical strains of Aeromonas salmonicida to sequester Fe3+ from the high-affinity iron chelators ethylenediaminedihydroxy-phenylacetic acid, lactoferrin, and transferrin was determined. Typical strains were readily able to sequester Fe3+ and used two different mechanisms. One mechanism was inducible and appeared to involve production of a low-molecular-weight soluble siderophore(s). Iron uptake by this mechanism was strongly inhibited by ferricyanide. One virulent strain displayed a second mechanism which was constitutive and required cell contact with Fe3+-lactoferrin or -transferrin. This strain did not produce a soluble siderophore(s) but could utilize the siderophore(s) produced by the other strain. Fe3+ uptake by this stripping mechanism was strongly inhibited by dinitrophenol. Atypical strains displayed a markedly reduced ability to sequester iron from high-affinity chelators, although one of them was able to utilize the siderophores produced by the typical strain. In all strains examined, Fe3+ limitation resulted in the increased synthesis of several high-molecular-weight outer membrane proteins.